2021
DOI: 10.1080/13854046.2021.1974565
|View full text |Cite
|
Sign up to set email alerts
|

Philips IntelliSpace Cognition digital test battery: Equivalence and measurement invariance compared to traditional analog test versions

Abstract: Objective: To collect evidence of validity for a selection of digital tests on the Philips IntelliSpace Cognition (ISC) platform. Method: A total of 200 healthy participants (age 50-80) completed both the ISC battery and an analog version of the battery during separate visits. The battery included the following screeners and cognitive tests: Mini-Mental State Examination (2 nd edition), Clock Drawing Test, Trail-Making Test (TMT), Rey Auditory Verbal Learning Test (RAVLT), Rey-Osterrieth Complex Figure Test (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
(50 reference statements)
1
11
0
Order By: Relevance
“…More importantly, the lack of correlations in individual differences between RCM and PAP on both measures show that the participants experienced the challenge to demonstrate their working memory span very differently between the remote digital task and the in-clinic task with a live administrator. By contrast, a relevant study that compared digit span assessments using an administrator in-clinic found only small effects of older adults' higher performance on PAP than on digital tests, and more significantly, fair to good comparability between participants' raw scores in the two tests (Vermeent et al, 2021). Interestingly, our pilot data from a new cohort of participants in a follow-up study, who ran both the RCM and PAP verbal digit span tasks in the laboratory during a one-session experiment using counterbalanced order for the method, support the interpretation that a majority of older adults are more comfortable responding to an in-person than remote assessment (Germine et al, 2019).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…More importantly, the lack of correlations in individual differences between RCM and PAP on both measures show that the participants experienced the challenge to demonstrate their working memory span very differently between the remote digital task and the in-clinic task with a live administrator. By contrast, a relevant study that compared digit span assessments using an administrator in-clinic found only small effects of older adults' higher performance on PAP than on digital tests, and more significantly, fair to good comparability between participants' raw scores in the two tests (Vermeent et al, 2021). Interestingly, our pilot data from a new cohort of participants in a follow-up study, who ran both the RCM and PAP verbal digit span tasks in the laboratory during a one-session experiment using counterbalanced order for the method, support the interpretation that a majority of older adults are more comfortable responding to an in-person than remote assessment (Germine et al, 2019).…”
Section: Discussionmentioning
confidence: 74%
“…Our design and analysis were concerned with testing the similarity in participants' performance between PAP and RCM versions of each task, and also the comparability of individual differences in participants' scores. Consistent with several recent and relevant reports that have compared digital methods of cognitive screening (Bjorngrim et al, 2019;Domen et al, 2019;Koenig et al, 2019;Sacco et al, 2019;Mackin et al, 2021;Vermeent et al, 2021), we use the similarity of mean PAP and RCM scores on a task to inform construct validity for the RCM version of that measure, and the comparability of participants' individual differences (PAP versus RCM) to inform inter-method reliability and validity of the RCM version of that measure. Our hypothesis was that pairwise comparisons of the data collected on each task (i.e., digital versus PAP versions) would not show statistically meaningful differences between versions, and we would interpret this finding as confirmation that participants experience the remotely collected RCM and inperson PAP tasks as being highly similar.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Assessments are distributed across the first and second days of the study. Some assessments are administered via a computer (e.g., Automated Neuropsychological Assessment Metric) 102 or iPad (e.g., Philips Intellispace Cognition) 103 to complement traditional tests and obtain granular performance metrics (e.g., reaction time). Pupillometry measurements are obtained to assess the integrity of pupil constriction and dilation—a metric of cognitive processing load tolerance.…”
Section: Methodsmentioning
confidence: 99%
“…The participants will not know on beforehand which test they will start with, only the test leaders will know. The chosen interval was guided by earlier studies comparing digitalised versus analogue tests of cognitive function in healthy participants people with a wash out period ranging from 30 min to 4 weeks between the studies 33 35 44. Data will be both electronically and manually, and the data forms will be kept at the university site in a locked cabinet.…”
Section: Methodsmentioning
confidence: 99%